2011
DOI: 10.1021/jm101404k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure−Affinity Relationships of Novel Dibenzylideneacetone Derivatives as Probes for β-Amyloid Plaques

Abstract: A new and extensive set of dibenzylideneacetone derivatives was synthesized and screened for affinity toward Aβ(1-42) aggregates. Structure-activity relationships revealed the binding of dibenzylideneacetones to be affected by various substituents. The introduction of a substituent group in the ortho position reduced or abolished the binding. However, the para position was highly tolerant of sterically demanding substitutions. Three radioiodinated ligands (6, 70, and 71) and two (18)F fluoro-pegylated (FPEG) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 39 publications
2
52
0
1
Order By: Relevance
“…Fluorescence molecular imaging is appealing for small animal studies because of its low cost, easy operation, and stable imaging probes. In the past decade, the development of fluorescent imaging probes for AD has been actively pursued, and several probes showed capacity for imaging Aβs (37)(38)(39)(40)(41)(42)(43)(44)(45) and Tau tangles (64) in mice. Nonetheless, none has been used to monitor the effectiveness of drug therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence molecular imaging is appealing for small animal studies because of its low cost, easy operation, and stable imaging probes. In the past decade, the development of fluorescent imaging probes for AD has been actively pursued, and several probes showed capacity for imaging Aβs (37)(38)(39)(40)(41)(42)(43)(44)(45) and Tau tangles (64) in mice. Nonetheless, none has been used to monitor the effectiveness of drug therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several NIRF probes for insoluble Aβs have been reported (37)(38)(39)(40)(41)(42)(43)(44)(45). It has been almost 10 y since the first report of NIRF imaging of Aβs by Hintersteiner et al in 2005 (41).…”
mentioning
confidence: 99%
“…Thus we designed molecular probes for nuclear medicinal imaging the distribution of aggregates of Aβ and hyperphosphorylated tau protein in the brain of a patient with AD, which satisfied the following requirements: 1) high blood-brain barrier permeability; 2) high and specific binding ability to Aβ and tau aggregates; and 3) rapid elimination from normal regions of the brain. Consequently, we succeeded in developing 18 F-labeled pyridyl benzofuran derivative, 18 F-FPYBF-2, as a probe for PET imaging of Aβ plaques [28][29][30][31][32][33][34][35][36] and 123 I-labeled benzo imidazopyridine (BIP) derivative, BIP-3, as a probe for SPECT imaging of tau aggregates [37][38][39][40][41] (Fig. 3).…”
Section: Molecular Imaging Of β-Amyloid Plaques and Taumentioning
confidence: 99%
“…Indeed, it was reported that several Aβ probes with single-digit nanomolar Ki values for the Aβ aggregates successfully stained the Aβ plaques in brain sections of the Tg2576 mice by in vitro autoradiography 25,26 . In addition, it has been shown that chalcone derivatives with a dimethylamino group at the third position can be used to visualize Aβ plaques by in vitro autoradiography 19,27 .…”
Section: In Vitro Autoradiographymentioning
confidence: 99%